Fitting ICT and Technical Writing Skill Into Teachers’ Production Programme for Achieving the Millennium Goals - Ozuruoke, A. A; Eniang, O. U (Mediterranean Journal of Social Sciences, 2011)
This paper puts forward another idea that can enhance the achievement of the educational goal with specific skill suchas introducing the course ‘Technical and Scientific writing for all students in Colleges of Education. The paper suggests somemeasures in the method of impacting the skill that can be improved upon for the realization of the national millenniumdevelopment goal in developing countries. It highlights the goals of teacher’s education in consonants with technical writing. Thepaper approaches the agitation in a semi-empirical style of presentation using such elements as statement of problem, purposequestions and significant of the idea. It further states the scope necessary for implementation of the agitated idea. The part thatteaching and learning play in this proposal and the specific perspective of each were fully explained and conclusion drawn withsummarized strong worded appraisal which agitates that Technical and Scientific Writing as a course be made compulsory to allstudents of teachers training programmes especially in Colleges of education.